Summation Process of Convolution Operators for Multivariables - Taş, Emre; Yurdakadim, Tuğba; Girgin Atlihan, Özlem (Sarajevo Journal of Mathematics, 2018)
In this paper, we study Korovkin type approximation results for a sequence of positive linear convolution operators defined on C([a; b]x[c; d]), the space of all continuous real valued functions on [a; b]x[c; d], with the use of A-summation process which includes both convergence and almost convergence. We also study rate of convergence of these operators.